The Arrangement of Dynastic Politics in Regional Head Elections in Indonesia - Paisol Burlian; Pepni Martabela; Muhamad Rifai (Fakultas Syariah dan Hukum UIN Raden Fatah Palembang, 2025)
The practice of dynastic politics has been going on for almost 20 years, arguably the first and longest-existing dynasty in Kediri Regency. The research questions in this paper are: how do political dynasties in Indonesia operate and maintain power? And how can political dynasties in Kediri Regency develop? This research explains the origins or history of this dynasty, which began with business affairs and then progressed to politics. In the development of this dynasty, only those closest to the party are capable and able to implement or continue programs that have been created and not yet implemented. Many relatives, from businessmen to officials, from the village to the regional level, are ready to help and serve this dynasty in order to obtain rewards. This dynasty will also continue to occur if the regulations or laws governing a democratic system do not undergo definite changes. Because of its inclusive and closed nature, a political dynasty is very difficult to find fault with. At first glance, there is nothing wrong with dynastic politics, especially when referring to the democratic principle that every citizen has the same right to be elected and to vote. However, it cannot be denied that the political dynasties that have developed so far have harmed the essence of democracy itself.